Task-oriented interventions for children with developmental co-ordination disorder - Miyahara, Motohide; Hillier, Susan L; Pridham, Liz; Nakagawa, Shinichi (Cochrane database of systematic reviews, 2017)
Developmental co-ordination disorder (DCD) is a common childhood disorder, which can persist into adolescence and adulthood. Children with DCD have difficulties in performing the essential motor tasks required for self-care, academic, social and recreational activities. To assess the effectiveness of task-oriented interventions on movement performance, psychosocial functions, activity, and participation for children with DCD and to examine differential intervention effects as a factor of age, sex, severity of DCD, intervention intensity, and type of intervention. In March 2017, we searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, 13 other databases, and five trials registers. We also searched reference lists, and contacted members of the mailing list of the International Conference on DCD to identify additional studies. We included all randomised controlled trials (RCTs) and quasi-RCTs that compared the task-oriented intervention with either an inactive control intervention or an active control intervention in children and adolescents aged four to 18 years with a diagnosis of DCD.Types of outcome measures included changes in motor function, as assessed by standardised performance outcome tests and questionnaires; adverse events; and measures of participation. All review authors participated in study selection, data extraction, and assessments of risk of bias and quality, and two review authors independently performed all tasks. Specifically, two review authors independently screened titles and abstracts to eliminate irrelevant studies, extracted data from the included studies, assessed risk of bias, and rated the quality of the evidence using the GRADE approach. In cases of ambiguity or information missing from the paper, one review author contacted trial authors. This review included 15 studies (eight RCTs and seven quasi-RCTs). Study characteristicsThe trials included 649 participants of both sexes, ranging in age from five to 12 years.The participants were from Australia, Canada, China, Sweden, Taiwan, and the UK.Trials were conducted in hospital settings; at a university-based clinic, laboratory, or centre; in community centres; at home or school, or both at home and school.The durations of task-oriented interventions were mostly short term (less than six months), with the total number of sessions ranging from five to 50. The length of each session ranged from 30 to 90 minutes, and the frequencies ranged from once to seven times per week.We judged the risk of bias as moderate to high across the studies. Some elements were impossible to achieve (such as blinding of administering personnel or participants). primary outcomesA meta-analysis of two RCTs and four quasi-RCTs found in favour of task-oriented interventions for improved motor performance compared to no intervention (mean difference (MD) -3.63, 95% confidence interval (CI) -5.88 to -1.39; P = 0.002; I = 43%; 6 trials, 169 children; very low-quality evidence).A meta-analysis of two RCTs found no effect of task-oriented interventions for improved motor performance compared to no intervention (MD -2.34, 95% CI -7.50 to 2.83; P = 0.38; I = 42%; 2 trials, 51 children; low-quality evidence).Two studies reported no adverse effects or events. Through personal correspondence, the authors of nine studies indicated that no injuries had occurred. secondary outcomesDue to the limited number of studies with complete and consistent data, we were unable to perform any meta-analyses on our secondary measures or any subgroup analysis on age, sex, severity of DCD, and intervention intensity. We have very little confidence in the effect estimate: the true effect is likely to be substantially different from the estimate of effect. The conclusions drawn from previous reviews, which unanimously reported beneficial effects of intervention, are inconsistent with our conclusions. This review highlights the need for carefully designed and executed RCTs to investigate the effect of interventions for children with DCD.